Exploring Diverse Estimation Methods for Newly Proposed Statistical Model: Applications and Insights - Aslam, Muhammad; Hussain, Zawar; Ullah, Naeem; Ullah, Kifayat (Scientific Inquiry and Review, 2025)
The current study presented a new proposition, named as ‘Log-Logistic (LogLogi) family’. Furthermore, the study offered notable features, statistical and reliability properties, as well as expansions of densities of the proposed family of distributions and estimation techniques for its parameters. Seven classical estimation approaches were discussed for parameter estimation of the proposed scheme. The simulation was conducted to assess the accuracy of model parameters using seven different estimation methodologies. Moreover, the applicability of the proposed family of distribution was established considering two sub-models by applying different goodness of fit tests on two datasets. The newly proposed model proved to be highly-adaptable and demonstrated superior performance compared to other models